Alpha-to-gamma phase transformation self-reinforcing of Alumina Ceramic Slit Array in Nd:YAG Laser Cutting Based on Vapor-to-melt Ratio Controlling. Issue 12 (15th June 2022) - Luo, Yonghao; Zhang, Weiye; Ning, Chenhong; Zhu, Xiaowu; Wang, Yueliang; Lu, Bingwen; Li, Yanhui; Zhang, Xinyue
Abstract: The greatest challenge in the subsequent processing of alumina ceramic slit arrays is the strength of the cutting wall. Because of its high brittleness, the fracture toughness of the wall has become one of the most important factors limiting the cutting quality. In the process of laser cutting alumina ceramics, α-γ reverse phase transformation is caused by the lattice dislocation effect due to instantaneous impact of high-energy beam, which can be induced in the heating/melting process and retained in the rapid cooling process. Generally speaking, due to the metastable characteristics of γ-Al2 O3 lattice structure, the density, hardness and mechanical strength of the phase change products are obviously lower than α-Al2 O3 . However, the looser structure endows γ-Al2 O3 with higher shear deformation component and fracture toughness, which potentially generates self-reinforcing effect when attached to the substrate. By controlling the material removal mode, i.e. vapor-to-melt ratio, the effects of different phase transformation content and distribution on the wall of slit array is discussed to reveal the phenomenon and mechanism of α-γ phase transformation self-reinforcing. The results show that the thickness of phase transformation layer and mass fraction of γ-Al2 O3 both decrease with the increase of rvmr and the existence of phase transformation layer will slightly reduce the Vickers hardness of residual molten layer. However, a thinner phase transformation layer can simultaneously enhance the fracture toughness of the slit wall. Through the observation of the micromorphology and the comprehensive evaluation of the mechanical properties of the slit wall, it can be concluded that, under the appropriate vapor-to-melt ratio parameters (stable state of the molten layer and good cutting quality), the material is removed in time, and a small amount of phase transformation products contained in the residual molten layer can produce a self-reinforcing effect on the cutting slit.